Use of improved dissemination strategies leading to high adoption of new drought tolerant barley variety (Kounouz) - CGIAR Research Program on Livestock (2019)
Two cooperatives and a seed enterprise have invested in multiplication of a newly-introduced drought tolerant barley variety, availing 1600 tons of certified seeds to the Tunisian seed market in 2019, far beyond the project intervention area. Randomized Control Trials (RCT) were used to identify the most effective dissemination strategies for adoption of this new variety. This is particularly important for the CGIAR since the low adoption rate of technologies is one of the major constraints in agricultural research.